Hypoxia in Cell Reprogramming and the Epigenetic Regulations - Nakamura, Nariaki; Shi, Xiaobing; Darabi, Radbod; Li, Yong (Frontiers in Cell and Developmental Biology, 2021)
Cellular reprogramming is a fundamental topic in the research of stem cells and molecular biology. It is widely investigated and its understanding is crucial for learning about different aspects of development such as cell proliferation, determination of cell fate and stem cell renewal. Other factors involved during development include hypoxia and epigenetics, which play major roles in the development of tissues and organs. This review will discuss the involvement of hypoxia and epigenetics in the regulation of cellular reprogramming and how interplay between each factor can contribute to different cellular functions as well as tissue regeneration.